Growth of Global Publishing Output of Health Economics in the Twenty-First Century: A Bibliographic Insight - Jakovljevic, Mihajlo (Michael); Pejcic, Ana V. (Frontiers in Public Health, 2017)
Background Strong growth of interdisciplinary sciences might find exceptional example in academic health economics. We decided to observe the quantitative output in this science since the beginning of the twenty-first century. Methods Electronic search of the published literature was conducted in four different databases: one medical database—MEDLINE/PubMed, two general databases—Scopus/Elsevier and Web of Science (WoS), and one specialized health economic database—NHS Economic Evaluation Database (EED). The applied combination of key words was carefully chosen to cover the most commonly used terms in titles of publications dealing with conceptual areas of health economics. All bibliographic units were taken into account. Results Within the time horizon from January 1, 2000 to December 31, 2016, without language or limitations on bibliographic unit types, we identified an output ranging approximately from 60,345 to 88,246 records with applied search strategy in MEDLINE/PubMed, Scopus/Elsevier, and WoS. In NHS EED, we detected 14,761 records of economic evaluations of health interventions during the period in which database was maintained and regularly updated. With slightly more than one-third of the identified records, USA clearly dominates in this field. United Kingdom takes a strong second place with about 12% of identified records. Consistently, USA and UK universities are the most frequent among the top 15 affiliations/organizations of the authors of the identified records. Authors from Harvard University contributed to the largest number of the identified records. Conclusion There is a clear evidence of both the upward stream of blossoming in health economics publications and its acceleration. Based on this bibliographic data set, it is difficult to distinguish the actual impact growth of this output provided dominantly by academia with modest contribution by pharmaceutical/medicinal device industry and diverse national government-based agencies. Further insight into the citation track record of these individual publications could provide helpful upgrade and a perspective on ongoing development.